Top thought leaders share their best innovation ideas. (FTPress Delivers, 2010)
"Fast, powerful, realistic solutions for jumpstarting innovation--whatever you sell, whatever industry you're in! Discover how to change the playing field, leverage your customers' insights and expertise, uncover huge unmet needs, craft great customer experiences, and much more!"--Resource description page.